Preparation and characterization of multilayered superfine fibrous mat with the function of directional water transport. Issue 29 (29th May 2019) - Xu, Jinhao; Xin, Binjie; Chen, Zhuoming; Liu, Yan; Zheng, Yuansheng; Zhang, Fuli
Abstract : Multilayered superfine fibrous mat with the function of directional water transport is prepared by dual-mode electrospinning. Abstract : Directional water transport in garment materials plays a pivotal role in maintaining human thermal and wet comfort. In the present work, a new type of multilayer fibrous mat with the specific function of directional water transport was prepared via the combination of melt-electrospinning and solution-electrospinning. The polypropylene (PP) fibrous layer prepared by melt-electrospinning technology was located in the inner layer (next to the skin), while the polyacrylonitrile-containing hydrophilic nano-silica particles (PAN-SiO2 ) layer with remarkable hydrophilicity was located in the outer layer, which could effectively transport water to the outer surface of the composites. Treatment of the as-prepared PAN-SiO2 /PP with an alkaline aqueous solution of dopamine not only increased the wettability of the PP layer, but also further improved the hydrophilicity of PAN-SiO2 . A layer of cotton woven mesh was added between the TPP layer and TPAN-SiO2 to form a sandwich structure in order to accelerate water transport in the bilayered fibrous mats. The directional water transport, mechanical flexibility, and permeability of the prepared multilayered superfine fibrous mat were characterized systematically. The experimental results exhibited that TPAN-SiO2 /cotton mesh/TPP exhibited an excellent accumulative one-way transport index (AOTI, 1071%), remarkable overall moisture management capacity (OMMC, 0.88), and reasonably high water vapor transport rate (WVT, 11.6 kg d −1 m −2 ), indicating it is a promising candidate for the development of novel textile materials for use in the field of sportswear for fast sweat release applications.